IMPLEMENTASI MULTIMEDIA VIDEO DAN POWERPOINT PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI KELAS V SDN PASIRKAMUNING I KECAMATAN TELAGASARI KABUPATEN KARAWANG - Marantika, Erick; Akil; Agus Susanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Advances in information technology in all fields currently result in rapid, dynamic changes and have a broad impact on the environment. One of them is related to education. Learning multimedia can be understood as a multimedia program that are applicable to the teaching process, namely to convey messages (knowledge, skills and attitudes) and ideas. , emotions, interest and willingness to learn to facilitate the teaching and learning process. One effort to create fun and creativity in learning is the use of multimedia video and PowerPoint learning methods resources educators may utilize to instructing and learning. The purpose of multimedia video and PowerPoint is to support communication and create an atmosphere that is not monotonous and boring. This study aims to determine how multimedia videos and PowerPoint are used in Islamic religious education lessons at SDN Pasirkamuning I class V. Using qualitative research can provide information and insight to researchers regarding multimedia video and powerpoint in learning Islamic religious education at SDN Pasirkamuning I class V able to attract the interest of students at SDN Pasirkamuning I, especially in class V, in acquiring religious instruction in Islam so that it can motivate other teachers to utilize multimedia video and powerpoint for learning.